ETS transcription factor ER81 is required for the Pacinian corpuscle development - Šedý, Jiří; Tseng, S; Walro, J. M; Grim, Miloš; Kučera, Jan (Developmental dynamics, 2006)
ER81, a member of the ETS family of transcription factors, is involved in processes of specification of neuronal identity, control of sensory-motor connectivity, and differentiation of muscle spindles. Spindles either degenerate or are abnormal in mutant mice lacking ER81. We examined whether ER81 is required for the development of another class of mechanoreceptors, the Pacinian corpuscle. ER81 was expressed by the inner core cells of the corpuscles, as reflected by expression of the lacZ reporter gene in Er81(+/lacZ) mutants, thereby suggesting a role for ER81 in the corpuscle development. No Pacinian corpuscles or their afferent nerve fibers were present in the crus of Er81 null mice at birth. Legs of mutant embryos examined at E16.5 were also devoid of the corpuscles, but not of their afferents. Thus, Pacinian corpuscles do not form, and their afferents do not survive, in the absence of ER81. A deficiency of dorsal root ganglia neurons expressing calretinin, a marker for neurons subserving Pacinian corpuscles, correlated with the absence of corpuscles and their afferents in Er81 null mice. These observations indicate a requirement for ER81 in the assembly of Pacinian corpuscles and the survival of the sensory neurons that innervate them. (c) 2006 Wiley-Liss, Inc.
Keywords: DNA vazebné proteiny; financování organizované; Animals; S100 Calcium Binding Protein G; biologické markery; transkripční faktory; Biomarkers; S100 kalcium vázající protein G; delece genu; Mice, Knockout; myši knockoutované; reportérové geny; Immunohistochemistry; Mice; Transcription Factors; myši; imunohistochemie; Financing, Organized; Lac Operon; Neurons, Afferent; Gene Deletion; Ganglia, Spinal; neurony aferentní; DNA-Binding Proteins; spinální ganglia; Vater-Paciniho tělíska; Pacinian Corpuscles; zvířata; Genes, Reporter; lac operon